Copper alloy for sliding member, sliding member, and method for producing copper alloy for sliding member
By forming a structure of the Mn-Fe-based composite sulfide phase dispersed in the bronze main phase in the copper alloy for sliding members, the problem in the prior art is difficult to provide excellent wear resistance while avoiding the addition of lead, and a copper alloy material with high wear resistance is achieved.
Patent Information
- Application Number
- CN202380058249.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-08-02
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to provide a copper alloy for sliding members with excellent wear resistance while avoiding the addition of lead (Pb).
The structure of the Mn-Fe-type composite sulfide phase with a specific atomic ratio dispersed in the parent phase composed of bronze is used, and the composite sulfide phase is formed in a Cu alloy composed of an appropriate amount of Mn, Fe, S and Sn, and is dispersed in the bronze parent phase.
It achieves excellent wear resistance while avoiding the addition of Pb, and is suitable for applications of sliding members.
Smart Images

Figure CN119604634A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a copper alloy for a sliding member, a sliding member, and a method for producing the copper alloy for a sliding member.
[0002] This disclosure claims the priority based on Japanese Patent Application No. 2022-126624 for which it applied on August 8, 2022, and cites all the contents described in the Japanese patent application No. Background Art
[0003] In a sliding member including a sliding surface that slides in contact with other members, a copper alloy for sliding members is sometimes used as a material constituting a region at least including the sliding surface. As a copper alloy for sliding members, a copper alloy containing Pb (lead) is known. In contrast, from the viewpoint of reducing the environmental burden, a copper alloy containing Cu instead of Pb has been proposed. 5 FeS 4 Copper alloy for sliding members (for example, refer to International Publication No. 2011 / 132703 (Patent Document 1)).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2011 / 132703 Summary of the invention
[0007] Problems to be solved by the invention
[0008] As described above, from the viewpoint of reducing environmental burden, copper alloys for sliding members that avoid the addition of Pb are required. One object of the present disclosure is to provide a copper alloy for sliding members that avoids the addition of Pb and has excellent wear resistance, and a sliding member that has excellent sliding characteristics by including the copper alloy for sliding members.
[0009] Methods used to solve problems
[0010] The copper alloy for sliding member disclosed in the present invention has a composition containing 0.4 mass % or more and 6 mass % or less of Mn (manganese), 0.3 mass % or more and 5 mass % or less of Fe (iron), 0.3 mass % or more and 3.5 mass % or less of S (sulfur), and 1 mass % or more and 15 mass % or less of Sn (tin), and the balance is composed of Cu (copper) and inevitable impurities. The copper alloy for sliding member disclosed in the present invention has a structure including a parent phase formed of bronze and a composite sulfide phase dispersed in the parent phase, the composite sulfide phase containing 40 atomic % or more and 75 atomic % or less of Mn, 3 atomic % or more and 30 atomic % or less of Fe, and 1 atomic % or more and 55 atomic % or less of S.
[0011] The manufacturing method of the copper alloy for sliding members disclosed in the present invention comprises: a step of preparing a mixed powder, a step of making a molded body, and a step of forming a structure. In the step of preparing the mixed powder, at least one of Cu powder, Cu alloy powder containing 10% by mass or more and 40% by mass of Sn, FeS powder and CuS powder, and at least one selected from Cu alloy powder containing 5% by mass or more of Mn, Fe-Mn alloy powder containing 60% by mass or more of Mn, and Mn powder are mixed into the following component composition, thereby preparing the mixed powder, wherein the component composition contains: 0.4% by mass or more and 6% by mass or less of Mn, 0.3% by mass or more and 5% by mass or less of Fe, 0.3% by mass or more and 3.5% by mass or less of S, and 1% by mass or more and 15% by mass or less of Sn, and the balance is composed of Cu and unavoidable impurities. In the step of making a molded body, the molded body is made by powder compacting the mixed powder. In the step of forming the structure, the formed body is heated to form a structure including a matrix phase formed of bronze and a composite sulfide phase dispersed in the matrix phase, the composite sulfide phase containing 40 atomic % to 75 atomic % of Mn, 3 atomic % to 30 atomic % of Fe, and 1 atomic % to 55 atomic % of S.
[0012] Effects of the Invention
[0013] According to the copper alloy for sliding members and the method for producing the same, it is possible to provide a copper alloy for sliding members having excellent wear resistance while avoiding the addition of Pb. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic perspective view showing the appearance of a hydraulic excavator.
[0015] Figure 2 This is a schematic plan view showing the structure of a crawler-type travel device included in a hydraulic excavator.
[0016] Figure 3 is an exploded view showing the structure of a track roller including a bushing.
[0017] Figure 4 is a schematic cross-sectional view showing the structure of the sleeve.
[0018] Figure 5 This is an optical microscope photograph showing the state of the metal structure of the copper alloy for sliding members.
[0019] Figure 6 This is a flowchart showing an outline of a method for producing a copper alloy for a sliding member.
[0020] Figure 7This is a schematic diagram for explaining the method of the wear resistance test.
[0021] Figure 8 This is a graph showing the relationship between the volume ratio of the composite sulfide phase in each sample and the wear resistance.
[0022] Explanation of symbols
[0023] 2 crawler, 3 crawler frame, 4 guide wheel, 5 sprocket, 6 track shoe, 7 outer link, 8 inner link, 9 crawler link, 10 supporting wheel, 11 supporting wheel, 20 bushing, 21 main body, 21A inner wall, 22 flange, 22A end face, 23 through hole, 28 base, 29 sliding layer, 51 sprocket tooth, 71 parent phase, 72 composite sulfide phase, 81 disc, 81A surface, 91 sliding layer, 92 base, 100 hydraulic excavator, 101 crawler travel device, 101A crawler, 103 rotating body, 104 working mechanism, 105 arm, 106 dipper arm, 107 bucket, 108 cab. DETAILED DESCRIPTION
[0024] [Overview of Embodiments]
[0025] The copper alloy for sliding members disclosed in the present invention has a composition comprising 0.4 mass % to 6 mass % of Mn, 0.3 mass % to 5 mass % of Fe, 0.3 mass % to 3.5 mass % to 3.5 mass % of S, and 1 mass % to 15 mass % of Sn, with the balance being Cu and inevitable impurities. The copper alloy for sliding members disclosed in the present invention has a structure comprising a parent phase formed of bronze and a composite sulfide phase dispersed in the parent phase, the composite sulfide phase containing 40 atomic % to 75 atomic % of Mn, 3 atomic % to 30 atomic % of Fe, and 1 atomic % to 55 atomic % of S.
[0026] The present inventors have studied the composition and structure of a copper alloy for sliding parts that avoids the addition of Pb, and as a result, have found that a copper alloy for sliding parts that avoids the addition of Pb and has excellent wear resistance can be obtained by adopting a structure in which a Mn-Fe-based composite sulfide phase is dispersed in a parent phase composed of bronze. Specifically, a copper alloy for sliding parts that has excellent wear resistance can be obtained by forming a structure in which a Mn-Fe-based composite sulfide phase (hereinafter, sometimes simply referred to as a "complex sulfide phase") having a specific atomic ratio is dispersed in a parent phase composed of bronze in a Cu alloy having a component composition containing appropriate amounts of Mn, Fe, S, and Sn.
[0027] Hereinafter, the reasons for limiting the component composition of the copper alloy for a sliding member of the present disclosure to the above range will be described.
[0028] Mn: 0.4 mass % or more and 6 mass % or less
[0029] Mn is an element required to form a Mn-Fe composite sulfide phase. If the Mn content is less than 0.4% by mass, it is difficult to properly form a Mn-Fe composite sulfide phase. On the other hand, if the Mn content exceeds 6% by mass, the total amount of sulfides formed increases and the structure becomes fragile. In addition, in the case of manufacturing a copper alloy for sliding components by a powder sintering method, there is a hidden danger of sweating (a phenomenon in which a liquid phase seeps out on the surface in the manufacture of a copper alloy for sliding components based on sintering). Therefore, the Mn content needs to be set to the above range. In addition, from the viewpoint of easily forming a sufficient amount of Mn-Fe composite sulfide phase, the Mn content is preferably set to 0.5% by mass or more. On the other hand, from the viewpoint of more reliably avoiding the embrittlement of the organization, the Mn content is preferably set to 5% by mass or less.
[0030] Fe: 0.3 mass % or more and 5 mass % or less
[0031] Fe is an element required to form a Mn-Fe composite sulfide phase. If the Fe content is less than 0.3% by mass, it is difficult to form a Mn-Fe composite sulfide phase in the amount required to ensure sufficient sliding properties. On the other hand, if the Fe content exceeds 5% by mass, the proportion of Fe dissolved in the Cu alloy increases. As a result, the hardness of the Cu alloy increases. Therefore, when a Cu alloy is used as a sliding component, the aggressiveness to the object material increases, and there is a risk of deterioration in sliding properties. Therefore, the Fe content needs to be set to the above range. From the viewpoint of easily forming a sufficient Mn-Fe composite sulfide phase, the Fe content is preferably set to 0.5% by mass or more.
[0032] S: 0.3 mass % or more and 3.5 mass % or less
[0033] S is an element required to form a Mn-Fe composite sulfide phase. If the S content is less than 0.3% by mass, it is difficult to properly form a Mn-Fe composite sulfide phase. On the other hand, if the S content exceeds 3.5% by mass, when a copper alloy for sliding components is manufactured by a powder sintering method, the amount of liquid phase generated increases, and excessive sintering is performed, which may result in the shape of the original formed body not being maintained. Therefore, the S content needs to be set to the above range. From the viewpoint of easily and properly forming a Mn-Fe composite sulfide phase, the S content is preferably set to 0.5% by mass or more. On the other hand, from the viewpoint of more reliably avoiding a reduction in the strength of the copper alloy, the S content is preferably set to 3.0% by mass or less.
[0034] Sn: 1 mass % or more and 15 mass % or less
[0035] Sn is an element constituting a parent phase formed of bronze. In manufacturing based on sintering, from the viewpoint of forming a liquid phase and facilitating sintering, the Sn content needs to be set to 1% by mass or more. On the other hand, if the Sn content exceeds 15% by mass, the strength of the copper alloy begins to decrease. Therefore, the Sn content needs to be set to the above range. From the viewpoint of making sintering easier, the Sn content is preferably set to 5% by mass or more. On the other hand, from the viewpoint of more reliably avoiding a decrease in the strength of the copper alloy, the Sn content is preferably set to 12% by mass or less.
[0036] Unavoidable impurities
[0037] In addition to the components intentionally added in the manufacturing process, as inevitable impurities, the copper alloy for sliding components sometimes contains elements other than the above. Phosphorus (P), which is an inevitable impurity, forms phosphides by combining with Fe, hinders the formation of Mn-Fe composite sulfide phases, and reduces the strength of the copper alloy. Therefore, the P content is preferably set to 0.03% by mass or less. In addition, in addition to P, elements such as Al (aluminum) and Si (silicon) are sometimes included in the copper alloy for sliding components as inevitable impurities. These elements are also preferably set to 0.1% by mass or less and 0.1% by mass or less, respectively. The total amount of inevitable impurities is preferably set to 0.5% by mass or less.
[0038] According to the copper alloy for sliding members disclosed herein, excellent wear resistance can be achieved while avoiding the addition of Pb by having a structure in which a Mn—Fe based composite sulfide phase having a specific atomic ratio is dispersed in a parent phase formed of bronze in the Cu alloy having the above-mentioned appropriate component composition.
[0039] In the copper alloy for sliding members, the bronze constituting the matrix phase may be a single phase of α phase. With this structure, high sliding characteristics can be obtained more reliably.
[0040] In the above copper alloy for sliding member, the ratio of the complex sulfide phase to the copper alloy for sliding member can be 3 volume % or more and 20 volume % or less. By setting the ratio of the complex sulfide phase to 3 volume % or more, high wear resistance can be more reliably obtained. By setting the ratio of the complex sulfide phase to 20 volume % or less, the phenomenon of liquid phase seeping out on the surface (sweating phenomenon) can be suppressed in the production of the copper alloy for sliding member by sintering.
[0041] The sliding member of the present disclosure is a sliding member including a sliding surface that contacts and slides with other members. The region of the sliding member at least including the sliding surface is composed of the above-mentioned copper alloy for sliding members of the present disclosure. According to the sliding member of the present disclosure, a sliding member can be provided whose sliding surface is composed of the copper alloy for sliding members that avoids the addition of Pb and has excellent wear resistance.
[0042] The manufacturing method of the copper alloy for sliding members disclosed in the present invention comprises: a step of preparing a mixed powder, a step of making a molded body, and a step of forming a structure. In the step of preparing the mixed powder, at least one of Cu powder, Cu alloy powder containing 10% by mass or more and 40% by mass of Sn, FeS powder and CuS powder, and at least one selected from Cu alloy powder containing 5% by mass or more of Mn, Fe-Mn alloy powder containing 60% by mass or more of Mn, and Mn powder are mixed into the following component composition, thereby preparing the mixed powder, the component composition containing: 0.4% by mass or more and 6% by mass or less of Mn, 0.3% by mass or more and 5% by mass or less of Fe, 0.3% by mass or more and 3.5% by mass or less of S, and 1% by mass or more and 15% by mass or less of Sn, and the balance is composed of Cu and unavoidable impurities. In the step of making a molded body, the molded body is made by powder compacting the mixed powder. In the step of forming the structure, the formed body is heated to form a structure including a matrix phase formed of bronze and a composite sulfide phase dispersed in the matrix phase, the composite sulfide phase containing 40 atomic % to 75 atomic % of Mn, 3 atomic % to 30 atomic % of Fe, and 1 atomic % to 55 atomic % of S.
[0043] According to the method for producing a copper alloy for a sliding member of the present disclosure, the copper alloy for a sliding member of the present disclosure described above can be easily produced.
[0044] [Example of specific implementation]
[0045] Next, an example of a specific embodiment of the copper alloy for sliding members and the sliding member disclosed in the present invention will be described with reference to the drawings. In the following drawings, the same or corresponding parts are denoted by the same reference numerals, and their description will not be repeated.
[0046] An example of an embodiment of the copper alloy for a sliding member and the sliding member of the present disclosure will be described by taking a case where the sliding member of the present disclosure is used as a bushing included in a crawler-type travel device of a hydraulic excavator which is a construction vehicle.
[0047] Figure 1 2 is a schematic perspective view showing the appearance of a hydraulic excavator. Figure 1 The hydraulic excavator 100 includes a crawler travel device 101, a rotating body 103, and a working mechanism 104. The hydraulic excavator body includes the crawler travel device 101 and the rotating body 103. The crawler travel device 101 includes a pair of crawlers 101A. The rotating body 103 is mounted on the crawler travel device 101 via a rotating mechanism on the upper part of the crawler travel device 101. The rotating body 103 includes a cab 108.
[0048] The working mechanism 104 is supported in the rotating body 103 so as to be movable in the vertical direction, and can perform operations such as digging sand and soil. The working mechanism 104 includes a boom 105, an arm 106, and a bucket 107. The base of the boom 105 is connected to the rotating body 103. The arm 106 is connected to the front end of the boom 105. The bucket 107 is connected to the front end of the arm 106. The boom 105, the arm 106, and the bucket 107 are driven by hydraulic cylinders, respectively, so that the working mechanism 104 can perform desired operations.
[0049] Figure 2 1 is a schematic plan view showing the structure of a crawler-type travel device included in a hydraulic excavator. Figure 2 The crawler travel device 101 includes a crawler track 2, a crawler frame 3, a guide wheel 4, a sprocket 5, a plurality of (seven in this case) track rollers 10, and a plurality of (two in this case) carrier rollers 11.
[0050] Crawler track 2 includes a plurality of crawler links 9 connected in an endless manner and track shoes 6 fixed to each crawler link 9. The plurality of crawler links 9 include outer links 7 and inner links 8. The outer links 7 and the inner links 8 are alternately connected.
[0051] The guide wheel 4, a plurality of (seven in this case) supporting rollers 10, and a plurality of (two in this case) supporting rollers 11 are mounted on the track frame 3 so as to be rotatable around their respective axes. When viewed from the center of the track frame 3, the sprocket 5 is arranged on the side opposite to the end portion on the side where the guide wheel 4 is mounted. The sprocket 5 is connected to a power source such as an engine, and is driven by the power source to rotate around the axis. A protrusion protruding radially outward, i.e., a plurality of sprocket teeth 51, is arranged on the outer peripheral surface of the sprocket 5. Each sprocket tooth 51 meshes with the track 2. Therefore, the rotation of the sprocket 5 is transmitted to the track 2. As a result, the track 2 is driven by the rotation of the sprocket 5 and rotates in the circumferential direction.
[0052] A guide wheel 4 is mounted on the end of the track frame 3 (the end on the side opposite to the side where the sprocket 5 is arranged). In addition, in the area of the track frame 3 sandwiched by the sprocket 5 and the guide wheel 4, a plurality of supporting rollers 10 are mounted on the ground contact side, and a plurality of supporting rollers 11 are mounted on the side opposite to the ground contact side. The guide wheel 4, the supporting roller 10, and the supporting roller 11 are in contact with the inner peripheral surface of the track 2 at the outer peripheral surface. As a result, the track 2 driven by the rotation of the sprocket 5 rotates in the circumferential direction while being guided by the guide wheel 4, the sprocket 5, the supporting roller 10, and the supporting roller 11.
[0053] Figure 3 is an exploded view showing the structure of a track roller including a bushing. Figure 4 is a schematic cross-sectional view showing the structure of the sleeve. Figure 3 As shown, the track roller 10 has a structure including a pair of bushings 20. Figure 3 and Figure 4 The sleeve 20 includes a main body 21 having a cylindrical shape, and a disc-shaped flange 22 connected to one axial end of the main body 21 and having an outer diameter larger than that of the main body 21. The central axis of the main body 21 coincides with the central axis of the flange. The sleeve 20 is formed with a cylindrical through hole 23 that passes through the main body 21 and the flange 22 in the axial direction. The central axis of the through hole 23 coincides with the central axis of the main body 21 and the flange 22. The sleeve 20 has a hollow cylindrical shape.
[0054] Reference Figure 4 The sleeve 20 includes a steel base 28 and a sliding layer 29 covering a part of the surface of the base 28. The sliding layer 29 is configured to constitute the inner wall 21A of the through hole 23 surrounding the sleeve 20 and the end face 22A of the flange 22 on the side opposite to the main body 21. The inner wall 21A and the end face 22A are sliding surfaces that contact and slide with other components. The steel constituting the base 28 is not particularly limited, and may be, for example, cold-rolled steel sheets such as JIS standard SPHC, soft steel such as JIS standard SS400, carbon steel for mechanical structures, alloy steel for mechanical structures, etc. The sliding layer 29 is formed of a copper alloy for sliding components. The copper alloy for sliding components contains 0.4 mass % or more and 6 mass % or less of Mn, 0.3 mass % or more and 5 mass % or less of Fe, 0.3 mass % or more and 3.5 mass % or less of S, and 1 mass % or more and 15 mass % or less of Sn, and the balance is Cu and unavoidable impurities.
[0055] Figure 5 This is an optical microscope photograph showing the state of the metal structure of the copper alloy for sliding members. Figure 5 The copper alloy for sliding components constituting the sliding layer 29 includes a parent phase 71 composed of bronze, and a composite sulfide phase 72 dispersed in the parent phase 71, wherein the composite sulfide phase 72 contains 40 atomic % or more and 75 atomic % or less of Mn, 3 atomic % or more and 30 atomic % or less of Fe, and 1 atomic % or more and 55 atomic % or less of S. The composite sulfide phase 72 may contain Cu. In the present embodiment, the parent phase 71 is an α-phase single phase. The proportion of the composite sulfide phase 72 in the copper alloy for sliding components is 3 volume % or more and 20 volume % or less. The composition of the sulfide constituting the composite sulfide phase 72 can be confirmed by, for example, Energy Dispersive Spectroscopy (EDS). In addition, the proportion of the composite sulfide phase 72 in the copper alloy for sliding components can be measured, for example, by image analysis based on a digital microscope.
[0056] The copper alloy for sliding members constituting the sliding layer 29 has a structure in which a Mn-Fe composite sulfide phase 72 having a specific atomic ratio is dispersed in a parent phase 71 formed of bronze in the Cu alloy having the above-mentioned appropriate component composition, thereby becoming a copper alloy having excellent wear resistance while avoiding the addition of Pb. In addition, the region including the inner wall 21A and the end surface 22A of the sleeve 20 as the sliding surface is composed of the copper alloy for sliding members of the above-mentioned present embodiment. As a result, the sleeve 20 becomes a sliding member whose sliding surface is composed of the copper alloy for sliding members having excellent wear resistance while avoiding the addition of Pb.
[0057] Next, an example of a method for producing the copper alloy for a sliding member according to the present embodiment will be described. Figure 6 2 is a flowchart showing an outline of a method for producing a copper alloy for a sliding member. Figure 6 In the manufacturing method of the copper alloy for sliding members of the present embodiment, first, as step S10, a raw material powder mixing step is performed. In this step S10, for example, (1) pure Cu powder, (2) Cu alloy powder containing 10 to 40% by mass of Sn, (3) at least one of FeS powder and CuS powder, and (4) at least one selected from Cu alloy powder containing 5% by mass or more of Mn, Fe-Mn alloy powder containing 60% by mass or more of Mn, and Mn powder are mixed in a manner that satisfies the composition of the copper alloy for sliding members of the present embodiment.
[0058] Next, as step S20, a forming step is performed. In this step, for example, the mixed powder obtained by mixing in step S10 is pressed into powder by a stamping machine including a mold having a cavity of a desired shape. Specifically, a molded body is obtained by filling the cavity with the mixed powder and performing powder pressing by a stamping machine. In the case of manufacturing a copper alloy for a sliding member joined to a steel plate, the molded body is placed on the steel plate. In addition, for example, the mixed powder may be spread on a flat steel plate in a manner to achieve a certain thickness instead of the above.
[0059] Next, as step S30, a sintering step is performed. In this step S30, the formed body obtained in step S20 is sintered using a sintering furnace. For example, while supplying a reducing gas atmosphere into the sintering furnace, the formed body is heated to a temperature range of 800°C to 1000°C and maintained for a given time. At this time, a Mn-Fe composite sulfide phase is formed in the parent phase composed of bronze by the liquid phase promoting reaction generated by sintering. The formed body placed on the steel plate in step S20 is bonded to the steel plate while sintering. In step S20, the mixed powder dispersed on the steel plate in a manner to achieve a certain thickness is sintered to form a sintered body and bonded to the steel plate. When the density of the obtained sintered body is insufficient, rolling can be performed using a rolling mill. In addition, in order to further increase the density, the above-mentioned sintering and rolling can also be repeated multiple times, for example, twice.
[0060] Next, as step S40, a finishing process is performed. This process is not a necessary process and can be performed as needed. For example, grinding, polishing, and other processing, sealing treatment, etc. can be performed on the surface of the copper alloy for sliding components as a sintered body. In addition, in order to use the copper alloy coated steel plate on which a layer of the copper alloy for sliding components as a sintered body is formed on the above-mentioned steel plate to make the sleeve 20, the following steps can be adopted. First, the copper alloy coated steel plate is cut into a rectangular shape. Then, the main body 21 is made by using a stamping machine to bend the copper alloy for sliding components into a cylindrical shape in such a way that the layer of the copper alloy for sliding components becomes the inner wall. In addition, the flange 22 is made by machining the copper alloy coated steel plate into a disc shape. Then, the two are joined by friction welding in such a way that the side of the flange 22 where the layer of the copper alloy for sliding components is formed becomes the opposite side of the main body 21, thereby obtaining the sleeve 20.
[0061] Through the above steps, the copper alloy for sliding components and the sleeve 20 as the sliding component of the present embodiment can be manufactured. It should be noted that, in the above embodiment, the case where only the region including the sliding surface of the sliding component is composed of the copper alloy for sliding components is described, but the entire sliding component can also be composed of the copper alloy for sliding components.
[0062] Example
[0063] The copper alloy for sliding members of the present disclosure was produced and an experiment to confirm the wear resistance was conducted. The procedure of the experiment is as follows.
[0064] Figure 7 This is a schematic diagram for explaining the method of wear resistance test. Figure 7A sample having a sliding layer 91 formed of the copper alloy for sliding members of the present disclosure bonded to a substrate 92 was prepared by the same procedure as in the above-mentioned embodiment. At this time, the volume ratio of the complex sulfide phase 72 was changed by changing the component composition of the copper alloy for sliding members constituting the sliding layer 91. In addition, for comparison, a sample having a sliding layer 91 not including the complex sulfide phase 72 was also prepared. The component compositions of the samples are shown in Table 1.
[0065]
[0066] The sample thus obtained was pressed against the surface 81A of the rotating disk 81, and the amount of wear of the sliding layer was measured. The amount of wear was electrically detected by a sensor included in the test device, and recorded over time without removing the sample from the test device. The disk 81 used was a disk formed of JIS standard SUJ2 (bearing steel). The disk 81 has a flat ring shape. The disk 81 was rotated at a speed of 0.5 m / s in the circumferential direction (in the direction of arrow α). The sample was pressed in the direction of arrow β in such a way that the sliding layer 91 was in contact with the surface (end face) 81A of the disk 81. Lubricating oil heated to 80°C was supplied to the contact portion between the sliding layer 91 and the disk 81 at 200 ml / min. The pressing load was increased in such a way that the contact surface pressure between the sliding layer 91 and the disk 81 increased step by step. Specifically, the contact surface pressure was maintained at 0.9 MPa, 1.9 MPa, 3.0 MPa, 3.8 MPa, 4.8 MPa, 6.6 MPa, 8.6 MPa, 10.5 MPa, 14.3 MPa, 18.2 MPa, 28.8 MPa, 37.6 MPa, 47.3 MPa, and 57.0 MPa in sequence, and the contact surface pressure was increased in stages (a total of 140 minutes). Then, the wear amount at the end of the test was obtained for each sample.
[0067] Figure 8 This is a graph showing the relationship between the volume ratio of the composite sulfide phase in each sample and the wear resistance. Figure 8 In the figure, the horizontal axis corresponds to the volume ratio of the complex sulfide phase. Figure 8 In FIG. 1 , the vertical axis corresponds to the wear amount. The wear amount is expressed as a relative value with the wear amount of the sample not containing the composite sulfide phase being set to 1. In addition, Figure 8 The dotted line in the figure represents the wear amount of a sample when the same wear resistance test was carried out using a sample of a conventional lead-containing copper alloy (lead bronze; JIS standard LBC2 (CAC602)).
[0068] Reference Figure 8 The wear loss of the sample with a composite sulfide phase ratio of 1.5 volume% ( Figure 8The data point A) is significantly less than that of the sample without sulfide, and has wear resistance comparable to that of lead bronze, which is an existing material. In addition, the wear amount ( Figure 8 The data point B) is lower than the wear amount of lead bronze as a conventional material, and it can be considered that it has excellent wear resistance. The low wear amount is maintained at least in the range where the ratio of the complex sulfide phase is 20 volume % or less (more specifically, 19.1 volume % or less). The above experimental results confirm that according to the copper alloy for sliding members disclosed in the present invention, it is possible to provide a copper alloy for sliding members having excellent wear resistance while avoiding the addition of Pb.
[0069] It should be noted that, in the above-mentioned embodiment, the copper alloy for sliding components of the present disclosure is applied to the sleeve included in the crawler-type travel device of the engineering machinery, but the use of the copper alloy for sliding components of the present disclosure is not limited to this, and can be applied to various uses requiring sliding characteristics and wear resistance. The copper alloy for sliding components of the present disclosure can be used as a material for hydraulic equipment parts such as a hydraulic cylinder block, a piston shoe, a bracket, a valve plate used in a hydraulic pump, and a side plate used in a gear pump.
[0070] It should be understood that the embodiments and examples disclosed this time are illustrative in all aspects and are not restrictive in any aspect. The scope of the present invention is defined by the claims, not by the above description, and is intended to include all changes within the meaning and scope equivalent to the claims.
Claims
1. A copper alloy for a sliding member, having the following composition, wherein the composition comprises: 0.4 mass % to 6 mass % of Mn, 0.3 mass % to 5 mass % of Fe, 0.3 mass % to 3.5 mass % of S, and 1 mass % or more and 15 mass % or less of Sn, and The balance consists of Cu and unavoidable impurities. The copper alloy for sliding members has the following structure, which includes: The parent phase is formed by bronze, and a composite sulfide phase dispersed in the parent phase, The composite sulfide phase contains 40 atomic % to 75 atomic % both inclusive of Mn, 3 atomic % to 30 atomic % both inclusive of Fe, and 1 atomic % to 55 atomic % both inclusive of S.
2. The copper alloy for sliding members according to claim 1, wherein The bronze constituting the parent phase is a single phase of α phase.
3. The copper alloy for sliding members according to claim 1, wherein The ratio of the complex sulfide phase to the copper alloy for a sliding member is 3 volume % or more and 20 volume % or less.
4. A sliding member comprising a sliding surface that contacts and slides with another member, wherein: At least a region including the sliding surface is made of the copper alloy for a sliding member according to any one of claims 1 to 3.
5. A method for producing a copper alloy for a sliding member, comprising: A step of preparing a mixed powder by mixing Cu powder, a Cu alloy powder containing 10 mass % or more and 40 mass % or less of Sn, at least one of FeS powder and CuS powder, and at least one selected from a Cu alloy powder containing 5 mass % or more of Mn, a Fe-Mn alloy powder containing 60 mass % or more of Mn, and a Mn powder into a component composition containing 0.4 mass % or more and 6 mass % or less of Mn, 0.3 mass % or more and 5 mass % or less of Fe, 0.3 mass % or more and 3.5 mass % or less of S, and 1 mass % or more and 15 mass % or less of Sn, with the balance being Cu and unavoidable impurities; A step of manufacturing a compact by compacting the mixed powder; and A step of heating the formed body to form a structure including a matrix phase formed of bronze and a composite sulfide phase dispersed in the matrix phase, the composite sulfide phase containing 40 atomic % to 75 atomic % of Mn, 3 atomic % to 30 atomic % of Fe, and 1 atomic % to 55 atomic % of S.
Citation Information
Patent Citations
Battery module supporting automated low-voltage charging
JP2022126624A
Copper alloy for sliding member
WO2011132703A1